Does cardiovascular risk vary according to the criteria for a diagnosis of polycystic ovary syndrome? - YOLDEMİR, AHMET TEVFİK; YAVUZ, DİLEK (WILEY, 2017)
AimThe risk of cardiovascular disease is higher in women with polycystic ovary syndrome (PCOS) compared to healthy individuals. Chronic inflammation, insulin resistance, hyperandrogenemia, hyperlipidemia and increased oxidative stress are known to have a role in the formation of atherosclerosis and cardiovascular disease. The aim of our study was to evaluate if cardiovascular risk varied according to different PCOS criteria, using carotid intima-media thickness (CIMT), which is an important marker of major cardiovascular events in the later stages of life. MethodsThe study group included 52 women aged 18-35 diagnosed with PCOS, and the control group comprised 45 age-matched healthy women. Body mass index, CIMT, fasting serum glucose and insulin levels and hormonal and lipid profiles were compared between the groups. ResultsThere was no significant difference in CIMT levels between the groups. The CIMT levels in the PCOS group did not differ whether hyperandrogenism, polycystic ovary-like appearance on ultrasound or oligo/anovulation status were present or not. Furthermore, when all cases were divided into subgroups according to BMI values, the CIMT values were similar between the groups. ConclusionBecause PCOS and atherosclerosis both have a complex nature, it is likely that the evaluation of CIMT alone may not be sufficient to determine endothelial dysfunction in a reproductive age group.
Keywords: body mass index; cardiovascular risk; carotid intima-media thickness; polycystic ovary syndrome; INTIMA-MEDIA THICKNESS; PREMATURE CAROTID ATHEROSCLEROSIS; YOUNG-WOMEN; ARTERIAL STIFFNESS; SUBCLINICAL ATHEROSCLEROSIS; INSULIN-RESISTANCE; VASCULAR FUNCTION; ANDROGEN EXCESS; SYNDROME PCOS; DISEASE RISK